GAMBARAN BODY IMAGE PADA ATLET REMAJA DI SEKOLAH SMP/SMA NEGERI RAGUNAN JAKARTA - Issom, Fitri Lestari; Putra, Putu Prajna Caesa (Journal of Research and Measurement in Psychology: JPPP, 2018)
The purpose of this study is to describe teenage athlete body image who study at State Ragunan Jakarta junior and senior high school. There are five dimensions related to body image such as Appearance Evaluation, Appearance Orientation, Body Area Satisfaction, Overweight Pre-occupation, and Self-Classified Weight. This study used ex-post facto method where participants were asked to fill in the MBSRQ-AS (Multidimensional Body Self Relations Questionnaires-Appearance Scale) trials and final data. Participants who involved in the trials are 65 people and from that the reliability of MBSRQ-AS is known for 0,77. For the final data participants who involved are 146 people. Participants is teenage around 12-18 years old. This study was conducted on June 2017 at State Ragunan Jakarta junior and senior high school. The results of this study obtained a conclusion that 55,5% teenage athlete who study at State Ragunan Jakarta junior and senior high school and involved in this study have a negative body image